Development of biocatalytic approaches and screening methodology for the synthesis of nitrogen-containing small molecules - Cairns, Ryan (2022)
As we move towards a more sustainable global economy, there is a need to develop efficient methods for the synthesis of key chiral molecules that are particularly vital for the pharmaceutical and agrochemical industries. Catalysis has opened up a plethora of synthetic opportunities and biocatalytsis, specifically, has now emerged as a sustainable alternative to other catalytic approaches. The application of amine transaminases (ATAs) for the conversion of pro-chiral carbonyls to the corresponding chiral amines in the presence of a suitable amine donor and the coenzyme pyridoxyl-5’-phosphate (PLP) has been well established. While their commonly cited limitations include narrow substrate scope and/or incompatible operational temperatures/pH, there is significant literature precedent for overcoming these challenges through enzyme engineering endeavours, which typically require reliable, high throughput selection assays.